How do analysts deal with bad news? Going-concern opinions and analyst behaviour - a systematic review - Peixinho, Ruben Miguel Torcato (Cranfield University, 2005)
This study systematically reviews the literature that can constitute the foundations for the connection of two areas that have hitherto been developed separately: analyst behaviour and going-concern opinions. Financial literature claims that analyst judgement is biased given their tendency to systematically underreact in the presence of bad news and their tendency to systematically overreact in the presence of good news. Considering that goingconcern modifications constitute an unambiguous and acute case of bad news, this event presents a unique opportunity to explore analysts' anticipation of and reaction to the presence of bad news. This analysis can provide further evidence on analysts' optimism and their role in the apparent delayed impact of bad news to investors. A systematic review of the literature is developed in order to guarantee methodological rigour in the review process. The systematic search for studies in the refined scope finds 40 papers that are analysed and synthesised. These papers are discussed in order to justify the potential gap in the literature and the research opportunities available for a doctoral study. The results suggest that the connection between these areas can sustain a doctoral study and contribute for the development of the accounting and finance framework.